The effect of nano encapsulated phase change materials and nanoparticles on turbulent heat transport: A conical diffuser scenario - Iachachene, Farida; Haddad, Zoubida; Arıcı, Müslüm; Abu-Nada, Eiyad; Sheremet, Mikhail A. (Journal of energy storage)
The present work investigates turbulent flow of single and hybrid nanofluids filled in a conical diffuser. The heat transfer coefficients and pressure losses are analyzed at various Reynolds numbers and nanoparticle volume fractions. The diffuser is filled with Al2O3, nano encapsulated phase change material NEPCM, and NEPCM_Al2O3 nanofluids. The thermophysical parameters of all nanofluids were determined using a novel methodology based on the thermodynamic equilibrium data for binary liquid mixtures. A notable novelty in the current work is the introduction of an innovative method of hybrid nanofluids composed of nanoparticles with and without phase change material (PCM). When compared to the other nanofluids tested, the NEPCM nanofluid presented the lowest pressure loss and the greatest heat transfer improvement within the diffuser. The Nusselt number of NEPCM nanofluids is enhanced by 15%, while for NEPCM_Al2O3 and Al2O3 nanofluids is increased by 10% and 6%, respectively. Similarly, the pressure drop is greater as compared to the base fluid, where the pressure drop is increased by 1%, 3.5%, and 5% for NEPCM, Al2O3 and NEPCM_Al2O3 nanofluid, respectively.